Colombia - Programmatic Strategic Engagement on Public Sector Management and Governance : Concept Note - World Bank (Washington, DC, 2013)
This concept note presents the strategic engagement of the World Bank in the areas of public sector management and governance in Colombia. It describes the short and medium term approach through which the Bank will provide support to the country on those areas of reform, as well as their links and synergies with other sectors activities. It also provides a summary of the Bank's public sector management and governance recent activities and their links with the program proposed by this strategy. This concept note lays out the strategy and program of financial support, knowledge and convening services to continue supporting the Government's public sector reform agenda in a demand-driven and flexible manner. The program aims to contribute to improve sustained and inclusive growth and competitiveness through strengthened government's management and improved service delivery. Its objectives are aligned with the National Development Plan (NDP) pillars and cross-cutting themes of good governance and regional development and integration, as well the Country Partnership Strategy (CPS) outcomes. The remainder of this note is structured as follows: (i) section two summarizes the trend public sector reforms have been following in Colombia; (ii) section three provides an overview of the trajectory the reform key National Government Management Institutions (NGMI) has followed in Colombia, summarizing the current status of Government's efforts in this area and outlining the pending policy reform agenda; (iii) section four presents a review of past Bank engagement in NGMI' s reforms and a description of the strategy to respond to the Government's priorities and pending reform agenda, including key expected outputs; (iv) section five provides an overview of the trajectory decentralization reform has followed in Colombia, summarizing the current status of Government's efforts in this area and outlining the pending policy reform agenda; (v) section six presents a review of past Bank engagement in decentralization reforms and a description of the strategy to respond to the Government's priorities and pending reform agenda, including key expected outputs; and, (vi) section seven contains a resource section, describing the timeline of proposed activities, budget, team composition, and processes for quality review, monitoring and evaluation.